2018
DOI: 10.1021/acs.jpcc.8b04459
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electrochemical Surface Potential and Irradiation on Garnet-Type Almandine’s Dissolution Kinetics

Abstract: Nanoscale-resolved quantifications of almandine's (Fe 3 Al 2 (SiO 4 ) 3 ) dissolution rates across a range of pHs (1 ≤ pH ≤ 13)established using vertical scanning interferometryreveal that its dissolution rate achieves a minimum around pH 5. This minimum coincides with almandine's point of zero charge. These trends in almandine's dissolution can be estimated using the Butler−Volmer equation that reveals linkages between surface potentials and dissolution rates, demonstrating proton-and hydroxyl-promoted brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 61 publications
2
25
1
Order By: Relevance
“…8 Such alterations can detrimentally affect the structural integrity of concretean issue of particular importance in nuclear power plants (NPPs). 6,7,[9][10][11] Volume changes produced in nuclear power plant concretes may result from expansion, drying shrinkage, and radiation (e.g., neutron, and γ-rays) effects on the aggregate and cement paste. Aggregates and the minerals therein, which occupy >70% of the volume of concrete and are disproportionately affected by radiation exposure, dominantly affect volume changes and the durability of concrete.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 Such alterations can detrimentally affect the structural integrity of concretean issue of particular importance in nuclear power plants (NPPs). 6,7,[9][10][11] Volume changes produced in nuclear power plant concretes may result from expansion, drying shrinkage, and radiation (e.g., neutron, and γ-rays) effects on the aggregate and cement paste. Aggregates and the minerals therein, which occupy >70% of the volume of concrete and are disproportionately affected by radiation exposure, dominantly affect volume changes and the durability of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Studies of irradiation-induced alterations of the atomic structure and reactivity of minerals have mainly focused on silicates such as quartz: SiO 2 , albite: NaAlSi 3 O 8 , and almandine: Fe 3 Al 2 Si 3 O 12which were observed to form disordered structures following their irradiation. 7,9,10 However, the effects of irradiation on carbonates remain less clear. For example, for calcite, whereas some studies reported negligible changes both in its atomic structure and dissolution kinetics, 7,14 others indicate an evolution toward an amorphous atomic structure with increasing fluence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanistic understanding and quantification of the density change of irradiated minerals is still a topic of ongoing research although recent progress was made thanks to atomistic modeling, e.g., such as molecular dynamics simulations of irradiated quartz, calcite, albite and almandine (Pignatelli et al 2016;Krishnan et al 2017b;Hsiao et al 2017Hsiao et al , 2018. Hence, the development of RIVE models can only be constructed, at this stage, from the empirical observation of the general swelling curves trends with fluence and irradiation temperature.…”
Section: Empirical Equationsmentioning
confidence: 99%